Social theoretical and conceptual historical aspects of the problem of acceleration of history. Reflections in the wake of Reinhart Koselleck - Schmieder, Falko (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
The article aims to contribute to the exploration of the topicality and the limits of Reinhart Koselleck’s approach to conceptual history. The concept of acceleration will serve as a guideline. It is of great relevance for Koselleck’s conceptual history as well as for his sociological work, because it plays a central role in his intervention in the debate on secularization and is closely related to the concept of temporalization, which was probably the most important element in Koselleck’s interpretation of the so-called saddle time. Since this is a social and time-analytical category, the more recent thesis of the entry into a post-Koselleckian culture, as advocated by contemporary historians and sociologists, should be able to unfold or be tested on the basis of this category itself. The paper first discusses the concept of acceleration and its implications for Koselleck, and then, on this basis, develops aspects and problems that go beyond Koselleck’s approach.